FARRELL, Amy Erdman. A Ms. Magazine e a promessa do feminismo popular. - Miguel, Raquel de Barros Pinto (Revista Estudos Feministas, 2006)
FARRELL, Amy Erdman. A Ms. Magazine e a promessa do feminismo popular.